Effect of Twelve Weeks Yoga and Physical Training on Selected Physiological Variables - Mukesh Kumar Taker, Dr. Pramjeet Singh Ghuman, Dr. Harbans Lal Godra (International Journal of Advanced Science and Technology, 2020)
With the change in the lifestyle in the 21st century, it has become imperative to strike a perfect coordination between heart, mind and soul to maintain sound health of mind. This is where Yoga plays its conclusive role to contribute to the wellbeing of human life. Yoga is a way of life to which brings the mental and physical faculties of people together to put at rest both mind and body. Keeping this universal truth in mind, a study on randomly selected students in the age group of 18-21 years was conducted to explore the impact of twelve weeks of regular yoga and physical training on physiological variables.